Trends in Neurovascular Interventions - Tsukahara, Tetsuya; Esposito, Giuseppe; Steiger, Hans-Jakob; Rinkel, Gabriel J.E; Regli, Luca (Acta Neurochirurgica Supplement,, 2014)
This book covers topical issues in neurovascular surgery, and in particular the management of intracranial aneurysms, arteriovenous malformations, and cavernomas, current trends in cerebral revascularization, and new concepts in cerebrovascular imaging. The contents reflect the continuing developments in interventions in cerebrovascular disorders as a result of progress in neuroimaging, evolution of pathophysiological concepts, new clinical trials, and technological innovations. The chapters are all written by acknowledged experts from across the world, and comprise original papers presented at the 6th European Japanese Stroke Surgery Conference, held in June 2012 in Utrecht, The Netherlands. The book will be of value to all who are interested in the latest developments in the field and offers fascinating insights into varied perspectives and techniques.